Changes in the composition of grass and shrub layer plants in common oak stands since the closure of leaf canopy - Ihor Ivanyuk; Tetiana Ivaniuk; Volodymyr Krasnov; Oleh Zhukovskyi (Наукові горизонти)
Nowadays, there are threats of extinction of plant communities and individual plant species. Therefore, it is important to investigate the possibilities of restoring the composition of plants of different levels of forest phytocoenoses after clear-cutting in specific types of forest conditions. The purpose of the study was to establish the possibilities and features of restoring the species composition of plants of the grass and shrub layer, new growth and undergrowth after closing of canopies on common oak stands in fresh sugruds. Methods used: species accounting, comparison of species diversity at different sites, assessment of species abundance. It was established that the grass and shrub layer in closed forest stands consists of 54-57 species and it has a significant foliage cover – 60%. The base of the layer consists of 18-20 species. There is an increase with age in the value of the foliage cover of the main types of grass and shrub layer from 57-58% to 63-68%. It was found that the largest number of plants of the grass and shrub layer belongs to the forest ecological and coenotic group: in 9-10-year-old stands, 53.5% of species belong to the group, in 20-40-year-olds – 66.0%, and in 50-60-year-olds – 69.2%. It was found that the undergrowth consists of 4-6 species with a total closeness of 20-30% in crops of all age groups. The new growth consists of 6-8 species in forest stands of all age groups and their foliage cover ranges from 20-25%. The ratio of plants of different ecological and coenotic groups in oak stands of 50-60 years is quite close to overripe (130-140 years) natural stands. The practical significance of the study lies in the possibility of using the results in the practice of creating environmental protection facilities and justifying the systems of harvesting for the general use